The analysis of SAKTI system implementation in government financial reporting using UTAUT approach - Agustina, Resti; Dewi, Fajar Gustiawaty; Dharma, Fitra (Lighthouse Publishing, 2025)
This research investigates the implementation of the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) in the financial reporting process of government agencies using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. The study was conducted on 60 work units within the Ministry of Religious Affairs in Lampung Province, involving 179 respondents, including treasurers, GLP operators, and fixed asset and inventory BMN operators. This research examines the influence of performance expectancy, effort expectancy, social influence, and facilitating conditions on individuals' behavioral intentions to use SAKTI and its impact on usage behavior. Data were collected through a questionnaire survey and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that performance expectancy, effort expectancy, and social influence positively affect behavioral intention, while facilitating conditions have a more direct impact on usage behavior. These findings provide practical implications for the government to enhance the adoption of accounting information systems and strengthen transparency and accountability in public financial management.